Phycobiotechnology : biodiversity and biotechnology of algae and algal products for food, feed, and fuel - Sangeetha, Jeyabalan; Thangadurai, D.; Elumalai, Sanniyasi, 1976; Thimmappa, Shivasharana Chandrabanda, 1976- (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press, Inc. ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This volume explores and explains the vast uses and benefits of algae as food, feed, and fuel. It covers the most advanced applications of algae in the food and feed industries and for environmental sustainability. With chapters written by experts and which were extensively reviewed by many well-known subject experts and professionals, Phycobiotechnology: Biodiversity and Biotechnology of Algae and Algal Products for Food, Feed, and Fuel provides an abundance of valuable information. Algae are a genetically diverse group of organisms with a wide range of physiological and biochemical characteristics that have unique capabilities in the fields of agriculture, pharmaceuticals, industry, and environment. Algae hold the potential to become the planet's next major source of energy and a vital part of the solution for climate change and dependence on fossil fuels. Many varieties of algae are also known to be an abundant source of vitamins, minerals, and other nutrients that can boost the human immune system. The algal industry is a booming sector and will continue to grow, and the editors state, it would not be wrong to call algae the most potent organism of the century due to its many applications and economic value. Key features of the book: Looks at the diversity and distribution of common seaweeds and microalgal biomarkers for hydrocarbon exploration, reviews microalgal bioactive compounds, biomolecules, and biofuels for sustainable development, discusses the health benefits of fucoidan (found in many species of brown seaweed) and the role of cyanobacteria against various human diseases, provides an evaluation of protocols for biomass recovery and lipid extraction by microalgae, defines DNA rearrangements in cyanobacterial nitrogen fixation, presents systematic insights into the biotechnological applications of microalgae and exploitation of omega-3 fatty acids, explores genetic engineering tools and metabolic engineering aspects of algae."--
Diversity and Distribution of Common Seaweeds from the West Coast of Maharashtra in India / Waghmode Ahilya Vitthal -- Microalgal Biomarkers for Hydrocarbon Explorationin Peninsular India / Thimarayan Sangeetha, Sanniyasi Elumalai, and Gopal Rajesh Kanna -- Bioactive Compounds from Algae / M. Jeya Bharathi -- Prospecting Microalgae for Biomolecules and Biofuels / Roshan Kumar, Sanniyasi Elumalai, and Sunil Pabbi -- Microalgal Biofuels: Current Status and Opportunities / Anurag Yadav and Kusum Yadav -- Biofuels from Microalgae: Future Bio-Energies for Sustainable Development / Ramganesh Selvarajan, Cecilia Oluseyi Osunmakinde, Timothy Sibanda, Anofi Ashafa, and Sanniyasi Elumalai -- Potential Health Benefits of Fucoidan: An Update / Thangaraj Vimala, Thinanoor Venugopal Poonguzhali, and Muthu Sakthivel -- Cyanobacteria as a Promising Source of Therapeutic Agents Against Various Human Diseases / Durdana Yasin, Nazia Ahmad, Moshahid Alam Rizvi, and Tasneem Fatma -- Evaluation of Methods of Biomass Recovery and Lipid Extraction for Microalgae / Mariana Lara Menegazzo, Jane Mary Lafayette Neves Gelinski, and Gustavo Graciano Fonseca -- DNA Rearrangements in Cyanobacterial Nitrogen Fixing Genes During Heterocyst Development / Neha Sami and Tasneem Fatma -- Determination of Kinetic Parameters for Biotechnological Applications With Microalgae / Nathanya Nayla De Oliveira, Mariana Lara Menegazzo, and Gustavo Graciano Fonseca -- Biotechnology of Microalgae: A Green Approach Towards Exploitation of Omega-3 Fatty Acids / Ramu Manjula and Manjunath Chavadi -- Genetic Engineering as a Tool for Improved Applications of Algae / Annamalai Jayshree -- Algal Pathways and Metabolic Engineering for Enhanced Production of Lipids, Carbohydrates, and Bioactive Compounds / Mohd. Azmuddin Abdullah, Hann Ling Wong, Syed Muhammad Usman Shah, and Pek Chin Loh.
OCLC-licensed vendor bibliographic record.
Keywords: Algae -- Biotechnology; Algae products; SCIENCE / General; SCIENCE / Biotechnology; SCIENCE / Life Sciences / Biology / Marine Biology